Fluffy's 100th day at school - McMullan, Kate (U.S.A : Scholastic, 1999)
Fluffy the guinea pig enjoys himself when Ms. Days class has a party to celebrate the one hundreth day of school.
Keywords: Guinea pigs -- fiction; Schools -- fiction